Linkages between gold and Latin American equity markets: Portfolio implications - Imran Yousaf; Hasan Hanif; Shoaib Ali; Syed Moudud-Ul-Huq (Journal of Economics, Finance and Administrative Science, 2021)
Purpose - The authors aim to examine the mean and volatility linkages between the gold market and the Latin American equity markets in the entire sample period and two crises periods, namely the US financial crisis and the Chinese crash. Design/methodology/approach - To examine the return and volatility spillovers, the authors employ VAR- BEKK-GARCH model on the daily data of four emerging Latin American equity markets which include Peru, Chile, Brazil and Mexico, which ranges from January 2000 to June 2018. Findings - The results show that the return transmissions vary across the stock markets and the crises periods. The volatility transmission is found to be bidirectional between the gold and stock markets of Brazil and Chile during the US financial crisis. Furthermore, the volatility spillover is unidirectional from Brazil to gold and from gold to Peru stock market during the Chinese crash. We also calculate the optimal weights hedge ratios for gold and stock portfolio. The result suggests that portfolio managers need to increase the weight of gold for the equity portfolios of Peru and Mexico during the US financial crisis. Furthermore, during the Chinese crisis, investors may raise the investment in gold for the equity portfolios of Brazil and Chile. Finally, the cheapest hedging strategy is CHIL/GOLD during the US financial crisis, whereas MEXI/GOLD during the Chinese crash. Practical implications - These findings have useful insights for portfolio diversification, asset pricing and risk management. Originality/value - The study's outcome provides policymakers and investors with in-depth insights regarding hedging, risk management and portfolio management.
Keywords: G10; G13; 330; Chinese equity market crash; Equity markets; Gold markets; US financial crises